Targeting breast cancer stem cells directly to treat refractory breast cancer - Pan, Liping; Han, Juan; Lin, Ming (Frontiers in Oncology, 2023)
For patients with refractory breast cancer (BC), integrative immunotherapies are emerging as a critical component of treatment. However, many patients remain unresponsive to treatment or relapse after a period. Different cells and mediators in the tumor microenvironment (TME) play important roles in the progression of BC, and cancer stem cells (CSCs) are deemed the main cause of relapse. Their characteristics depend on their interactions with their microenvironment as well as on the inducing factors and elements in this environment. Strategies to modulate the immune system in the TME of BC that are aimed at reversing the suppressive networks within it and eradicating residual CSCs are, thus, essential for improving the current therapeutic efficacy of BC. This review focuses on the development of immunoresistance in BCs and discusses the strategies that can modulate the immune system and target breast CSCs directly to tackle immunoresistance in refractory BC.